PENINGKATAN KESEHATAN GIZI MELALUI DAPUR SEHAT ATASI STUNTING - Samsuri; Suci, Ida Ayu; Zalviwan, Muhammad (LPPM Universitas Panca Bhakti, 2024)
Stunting is a condition of growth failure in children under five due to chronic malnutrition during the first 1,000 days of life (HPK). This condition is characterized by a child's height that is lower than the standard for their age. In Mempawah District, the prevalence of stunting has increased from 25.1% in 2022 to 27.2% in 2024, reflecting a serious problem in child nutrition. Sungai Duri II Village, Sungai Kunyit Sub-district, with a population of children under five who are vulnerable to stunting, is the focus of health interventions. Factors such as lack of access to nutritious food, poor quality of sanitation, and lack of parental knowledge are the main causes of stunting in this area. Collecting data on the health of children under five in Sungai Duri II Village is important as a basis for planning appropriate intervention programs. Through the improvement of basic health services, the role of posyandu, and health counseling, it is hoped that Sungai Duri II Village can become a model of success in overcoming stunting and improving the welfare of children under five